Board performance in strategic monitoring: Evidence from Portugal - Carvalheira, V.; Amaral-Baptista, M.; Esperança, J.; Melo, M.; Macedo-Soares, T. (17th Annual international Conference Global Business and Technology Association - GBATA 2015, 2015)
Despite the growing interest in the performance of boards of directors, most studies in the field concentrate on board structure instead of the ways they actually work. Few studies have shed light on how the work practices of boards may influence their performance on strategic tasks. In particular, no studies have analysed the Portuguese context in this regard. This paper analyses the influence of non-structural factors that may affect the effectiveness of Portuguese boards in the task of strategic monitoring. To do so, a replication study was conducted with basis on the model developed by Amaral-Baptista (2013) in the context of Brazilian firms. To test the model in the Portuguese empirical setting, a survey with 105 non-executive directors of Portuguese companies was conducted in 2014. The results showed that 67% of the variance observed in Board Effectiveness in Strategic Monitoring was explained by the antecedents Chairperson Leadership, Attention to Strategic Monitoring and Work Dynamics. Although Access to Information had a significant and positive influence on Business Knowledge, the effects of these factors on Board Effectiveness in Strategic Monitoring were not confirmed. These findings were generally consistent with the results of Amaral-Baptista (2013). The study is concluded with implications for management practice and future studies.